Contributions to the theory of games. - Berge, C. (Annals of mathematics studies, 1957)
A new group of contributions to the development of this theory by leading experts in the field. The contributors include L.D. Berkovitz, L.E. Dubins, H. Everett, W.H. Fleming, D. Gale, D. Gillette, S. Karlin, J.G. Kemeny, R. Restrepo, H.E. Scarf, M. Sion, G.L. Thompson, P. Wolfe, and others.